The PDCA Approach with Seven Quality Tools for Quality Improvement Men’s Formal Jackets in Indonesia Garment Industry - Sjarifudin, Didin; Kurnia, Hibarkah (TALENTA Publisher, 2022)
Garment production with men's jacket products still finds products with poor quality and a high percentage of defects. The method used in this study is the PDCA approach with seven quality tools. The purpose of this study is to determine the cause of defects, provide solutions to repair these problems by reducing product defects, and reduce the percentage of dominant defects in the Finishing section. This study found that the factors causing the damage were human, machine, method, material, and environmental factors. Meanwhile, improvement efforts are contained in the Action stage, namely 5W+1H. The results of these improvements have an impact on the reduction of finishing defects from 17.8% to 11.8% which means a decrease in defects by 33.7% every month in the finishing section. The implications of this research can be used as a reference to reduce similar problems in the garment industry process. The combination of the PDCA approach and seven repair tools results in a defect percentage control system using a control chart so that defects will be controlled and corrective actions will be taken quickly.